2020
DOI: 10.1038/s41598-020-75757-4
|View full text |Cite
|
Sign up to set email alerts
|

Helminth eggs from early cretaceous faeces

Abstract: The exceptional fossil site of Las Hoyas (upper Barremian, Cuenca, Spain) yields abundant small to medium vertebrate coprolites, hindering the search for parasites. We studied the contents of 29 coprolites that were previously classified into distinct morphotypes. Several parasitic eggs were retrieved from two of these coprolites, confirming the second record of digenea trematode eggs and nematode (ascaridid) eggs from an Early Cretaceous locality. The cylindrical coprolite containing anisakid eggs was likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The discovery of at least six parasites with at least five different morphotypes in a single coprolite suggests that multi-parasite infection was common had already diversified by the late Triassic. The presence of the Ascaridida eggs and the evidence for multi-infection found in the coprolite can presumably be explained by the predatory habits of the host, which would have been parasitized by feeding on parasitized fishes, amphibians, or other reptiles [ 3 , 4 , 18 ].…”
Section: Discussion and Systematic Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The discovery of at least six parasites with at least five different morphotypes in a single coprolite suggests that multi-parasite infection was common had already diversified by the late Triassic. The presence of the Ascaridida eggs and the evidence for multi-infection found in the coprolite can presumably be explained by the predatory habits of the host, which would have been parasitized by feeding on parasitized fishes, amphibians, or other reptiles [ 3 , 4 , 18 ].…”
Section: Discussion and Systematic Assessmentmentioning
confidence: 99%
“…Several reports have described parasite eggs in coprolites [ 3 6 , 8 , 18 ]. The assignment of coprolites to a specific host is challenging, but their different shapes can provide systematic information [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is hypothesised that, before adaptation to vertebrate hosts, these trematodes parasitised molluscs [13]. Some excavations revealed that Digenean trematodes can be found in dinosaur coprolites and mollusc fossils from the Upper (Late) [17] and Lower (Early) [18,19] Cretaceus periods; nevertheless, Cretaceous-Paleogene Mass Extinction (KPgME) around 66 million years ago (MYA) swept away most host species with their parasites [16].…”
Section: The Cretaceous-paleogene Boundarymentioning
confidence: 99%